Profile of Cybernetic Thinking of Students in Mathematical Problem Solving Based on Serialist and Holist Thinking Style - Yanti, Aning Wida; Kusaeri, Kusaeri; Kustianingsih, Mia (Universitas Muhammadiyah Mataram, 2020)
This research aim to describe the profile of cybernetic thinking of students in solving algebra problems. This research is a descriptive study with a qualitative approach using questionnaires, written tests, and interview guidelines. Intake of subjects who have Serialist and Holist thinking styles have done using purposive sampling. The results showed students who have the Serialist thinking style at the time of the Sensory Register's attention and good perception so that information stored in Short Term Memory. Retrieval done well even when rehearsal has difficulty because of forgetting certain concepts, but information has been stored well in Long Term Memory. The encoding done well. While students who have Holist style of thinking lack attention and perceptions are not structured so that information is not stored correctly in Short Term Memory. So that retrieval can not be done correctly. Therefore during rehearsal, they have difficulty in applying the settlement method because the information is not stored correctly in Long Term Memory.